Masticatory Function of Subjects Rehabilitated with Conventional Complete Denture - Marisa Martins da Silva PRADO; Tânia de Freitas BORGES; Célio Jesus do PRADO; Vanderlei Luiz GOMES; Flávio Domingues das NEVES (Association of Support to Oral Health Research (APESB), 2006)
Objective: Evaluate masticatory function of subjects rehabilitated with conventional complete denture, considered adequate or good (index of Kapur), by means of objective and subjective tests and to verify influence of quality and denture time use. Method: Masticatory performance tests (MP), using test food Optocal, had been carried through with 20 and 40 chewing strokes in 21 subjects with complete denture (group CD) and 15 with natural dentition (group ND). Masticatory performance index was taken by means of the calculation of the Average Geometric Diameter of chewed and sifted particles. Results: After analysis statistics (Tukey b, p<0.05), observed that group CD obtainable 12% and 31% of the performance reached for group ND subjects, after 20 and 40 strokes, respectively, being that literature quantifies masticatory performance from 20% to 30% of the natural dentition. Statistical significant differences (t-test student, p<0.05) between MP and masticatory ability had not been verified, as well as denture quality of group CD. In relation to denture use period, users with more than six months had obtainable better resulted, possibly for being more adapts to the denture. Conclusion: In the limit of this study, it could be possible conclude that complete dentures users considered adequate or good had improved its MP after use six months. Standing out that with 20 strokes, in test food related, the result (12%) was worst to in literature described.